Utilization of Organics, Amendment and Fertilizers with Sodic Water Irrigation: Long-Term Effect on Soil Properties and Rice-Wheat Productivity - D.R. Sharma, N.P.S. Yaduvanshi (Journal of the Indian Society of Soil Science, 2016)
The effects of organic manures namely, farmyard manure (FYM) and sulphitation pressmud (SPM) along with chemical amendment (gypsum) and fertilizer NPK (120-26-42 kg ha-1) were evaluated on the yields of rice and wheat and the changes in soil properties under sodic water irrigation. Results showed significant decrease in yield of rice and wheat in treatment receiving the fertilizer alone compared to combined use of organic manures, gypsum and NPK. Combined application showed significant increases in yield of rice (104%) and wheat (158%) compared with control, whereas NPK alone brought an increase of about 85 per cent in rice yield and 121 per cent in wheat yield over control. Gypsum application at 5 t ha-1 along with NPK significantly increased rice and wheat yield which was at par with application of SPM or FYM at 10 t ha-1 along with NPK. The fertility status of the soil also improved significantly in the combined treatments as compared to NPK fertilizer alone. The soil organic carbon was significantly higher in the organic manure (FYM and SPM) treatment, with increases of 27.5 and 32.5 per cent, respectively over the initial content. This study indicated that combined use of NPK and organics (SPM or FYM) positively influenced the fertility of soil and supported better yield of rice and wheat. Also FYM or SPM application may replace the gypsum which is relatively costlier.